2022
DOI: 10.1155/2022/6175053
|View full text |Cite|
|
Sign up to set email alerts
|

LINC01426 Triggers Growth and Metastasis of Lung Adenocarcinoma as a Prognostic Indicator

Abstract: The vital regulation of abnormally expressed lncRNAs in human cancers has been identified. This study is aimed at illustrating the role of LINC01426 in influencing malignant behaviors of lung adenocarcinoma (LUAD) and the possible mechanism. Differential expressions of LINC01426 in a downloaded profile containing LUAD and normal tissues were analyzed using Gene Expression Profiling Interactive Analysis (GEPIA) database and were reconfirmed in clinical samples collected in our hospital. In addition, LINC01426 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…LINC00894 enhances cell proliferation and invasion by binding with miR-429 to mediate ZEB1 expression in breast cancer ( Meng, Shao & Feng, 2021 ); what’s more, in thyroid cancer, its increased expression reduces the oncogenic properties by sponging let-7e−5p to promote TIA-1 expression ( Chen et al, 2022a ). LINC01426 modulates CTBP1/miR-423-5p/FOXM1 axis via interacting with IGF2BP1 to aggravate ccRCC progression ( Jiang et al, 2021b ), it also aggravates the malignant progression through miR-661/Mdm2 axis in glioma ( Shu et al, 2022 ), it serves as a prognostic indicator in lung adenocarcinoma by triggering growth and metastasis ( Deng et al, 2022 ), what’s more, in a recently reported study on ferroptosis-related lncRNAs of glioma, LINC01426 was identified to be related to ferroptosis, its knockdown could significantly increase in the Fe 2+ levels and the erastin-induced ROS levels in glioma cells ( Huang et al, 2022 ). LncRNA DUXAP8 acts as an oncogene in most tumors, its abnormal overexpression is associated with the proliferation, invasion, migration, anti-autophagy, and poor prognosis of tumors ( Wang et al, 2022a ; Wang et al, 2022b ), it may act as a potential therapeutic target for cancer ( Wang et al, 2022b ); in a research on identification of necroptosis-related lncRNAs in hepatocellular carcinoma, DUXAP8 was identified as a prognostic lncRNA and related to patients’ prognosis ( Chen et al, 2022b ); In addition to our research, other studies have also found that it is involved in the process of ferroptosis in tumor, such as: it can act with ferroptosis-associated gene FANCD2 to form DUXAP8-miR-29c-FANCD2 axe in hepatocellular carcinoma ( Yang et al, 2022 ), it was also identified as one of ferroptosis-related lncRNAs in kidney carcinoma ( Xing et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…LINC00894 enhances cell proliferation and invasion by binding with miR-429 to mediate ZEB1 expression in breast cancer ( Meng, Shao & Feng, 2021 ); what’s more, in thyroid cancer, its increased expression reduces the oncogenic properties by sponging let-7e−5p to promote TIA-1 expression ( Chen et al, 2022a ). LINC01426 modulates CTBP1/miR-423-5p/FOXM1 axis via interacting with IGF2BP1 to aggravate ccRCC progression ( Jiang et al, 2021b ), it also aggravates the malignant progression through miR-661/Mdm2 axis in glioma ( Shu et al, 2022 ), it serves as a prognostic indicator in lung adenocarcinoma by triggering growth and metastasis ( Deng et al, 2022 ), what’s more, in a recently reported study on ferroptosis-related lncRNAs of glioma, LINC01426 was identified to be related to ferroptosis, its knockdown could significantly increase in the Fe 2+ levels and the erastin-induced ROS levels in glioma cells ( Huang et al, 2022 ). LncRNA DUXAP8 acts as an oncogene in most tumors, its abnormal overexpression is associated with the proliferation, invasion, migration, anti-autophagy, and poor prognosis of tumors ( Wang et al, 2022a ; Wang et al, 2022b ), it may act as a potential therapeutic target for cancer ( Wang et al, 2022b ); in a research on identification of necroptosis-related lncRNAs in hepatocellular carcinoma, DUXAP8 was identified as a prognostic lncRNA and related to patients’ prognosis ( Chen et al, 2022b ); In addition to our research, other studies have also found that it is involved in the process of ferroptosis in tumor, such as: it can act with ferroptosis-associated gene FANCD2 to form DUXAP8-miR-29c-FANCD2 axe in hepatocellular carcinoma ( Yang et al, 2022 ), it was also identified as one of ferroptosis-related lncRNAs in kidney carcinoma ( Xing et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interference with LINC01426 expression reduces the proliferation and metastatic capacity of LUAD H1299 and PC9 cells [15] . VIM-AS1 has been shown to be associated with cancer metastasis and poor patient prognosis [7][8][9][10][16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple projects have shown that lncRNAs are associated with the prognosis and the growth of cancer cells [12][13][14][15] . Glioma tissues and cells showed signi cant downregulation of p53 expression and a signi cant increase in lncRNA PVT1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%